Haemato-biochemical alterations during different stages of lactation in Mehshani buffaloes - Das, Hemen; Lateef, A.; Panchasara, H.H.; Ali, M. Ayub (Buffalo Bulletin, 2016)
The present study was carried out to investigate the haemato-biochemical profile of Mehshani buffalo, a native breed of Gujarat, India with the purpose of analyzing the physiological variations under the influence of different lactation stages in terms of determining possible biomarkers to monitor the energetic balance and the metabolic adequacy during lactation. Eighteen clinically healthy lactating buffaloes were categorized into three groups based on the length of their lactation: group I (early stage), group II (mid stage) and group III (late stage). Non significant variations were observed in case of the hematological parameters amongst the three groups of animals. The packed cell volume (PCV), RBC count and haemoglobin (Hb) concentration was lowest in the buffaloes of the early stage of lactation. Other haematological parameters viz. total leucocyte count (TLC), differential leucocyte count (DLC), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and platelet count were recorded to be within the normal limits. Similarly, the values of the blood biochemical analytes varied apparently, but the differences were statistically non significant amongst the groups studied. The glucose level was recorded to be the lowest in the early stage of lactation; whereas, the protein and creatinine concentrations were slightly higher in this stage. No significant alteration in the concentration of Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline phosphatase (ALP) was noticed amongst the three groups of buffaloes under the current study. Data generated during the current study may be useful as reference values for the scientific community as this is the first study of its kind in case of Mehshani buffalo.